Hyphal growth and mycorrhiza formation by the arbuscular mycorrhizal fungus Glomus claroideum BEG 23 is stimulated by humic substances - Gryndler, M; Hrselová, H; Sudová, R; Gryndlerová, H; Rezácová, V; Merhautová, V (Mycorrhiza, 2005)
Effects of humic substances (humic acid or fulvic soil extract) or saprophytic microorganisms (Paecilomyces lilacinus and an unidentified actinomycete) on growth of mycelium and mycorrhiza formation by Glomus claroideum BEG23 were studied in a hydroponic system. Humic substances stimulated root colonization and production of extraradical mycelium by the mycorrhizal fungus. Both humic and fulvic acids tended to decrease populations of culturable bacteria and fungi in the cultivation system, indicating a moderately antibiotic activity. The addition of saprophytic microorganisms able to use humic substances to the cultivation system further stimulated the development of the mycorrhizal fungus. However, stimulation of G. claroideum was also observed when the saprophytic microorganisms were heat-killed, suggesting that their effect was not linked to a specific action on humic substances. The results indicate that humic substances may represent a stimulatory component of the soil environment with respect to arbuscular mycorrhizal fungi.
Keywords: kořeny rostlin; houby; kukuřice setá; benzopyrany; Zea mays; Hyphae; Fungi; Plant Roots; hyfy; Anti-Bacterial Agents; huminové látky; Bacteria; mykorhiza; Colony Count, Microbial; Humic Substances; Benzopyrans; počet mikrobiálních kolonií; antibakteriální látky; Mycorrhizae; antifungální látky; Antifungal Agents